Respuesta :
Answer:
t=
2
5
Step-by-step explanation:
First step:5t−7−t=3. Subtract t from both sides
Second step:4t−7=3. Combine 5t and −t to get 4t
Third step:4t=3+7. Add 7 to both sides
Fourth step:4t=10 Add 3 and 7 to get 10
Fifth step:t= Divide both sides by 4.
4
10
Six step:t= Reduce the fraction
4
10
to lowest terms by extracting and canceling out 2
2
5
Answer:
c = - 13 , t = - 11
Step-by-step explanation:
given the system of equations
2c - 3t = 7 → (1)
4c - 5t = 3 → (2)
multiplying (1) by - 2 and adding the result to (2) will eliminate c
- 4c + 6t = - 14 → (3)
add (2) and (3) term by term to eliminate c
(4c - 4c) + (- 5t + 6t) = 3 - 14
0 + t = - 11
t = - 11
substitute t = - 11 into either of the 2 equations and solve for c
substituting into (1)
2c - 3(- 11) = 7
2c + 33 = 7 ( subtract 33 from both sides )
2c = - 26 ( divide both sides by 2 )
c = - 13
The solution is c = - 13 , t = - 11